Peran Bidang Penyelenggara Haji dan Umrah Kementerian Agama Kabupaten Sumedang dalam Pelayanan Pendaftaran Haji Tahun 2023 - Aprilliani, Arindika; Barhrudin, Barhrudin; Yuningsih, Yuyun (Mabrur: Academic Journal of Hajj and Umra, 2024)
The purpose of the study was to determine the regulations, concepts, and behavior of officers from the Hajj and Umrah Organizer of the Ministry of Religion of Sumedang Regency in serving Hajj registration in 2023. The method used is qualitative method. The theory used is Levinson's role theory. The results of the interview show that there are other regulations in the Minister of Health Circular Letter Number.02.01/Menkes/33/2020 for pilgrims who have registered but when in the waiting period have a history of illness in the circular letter can delegate or cancel the hajj registration. PHU Kemenag Sumedang has two concepts in Hajj registration, namely direct registration and online registration through the Hajj smart application. Officer behavior in Hajj registration services must be in accordance with officer operational standards.